Hubungan Antara Kepribadian Big Five Terhadap Intensi Berwirausaha Pada Mahasiswa Fakultas Psikologi Universitas Muhammadiyah Surakarta - Prabowo, Alfan Ageng, Aad Satria Permadi, S.Psi, MA (2016)
Indonesia is one country that has difficulties in economic growth and the amount of the unemployment rate among educated people. entrepreneurship can be used as a benchmark to measure the health of the economy that is built by a community. The number of entrepreneurs in Indonesia is still small, about 1.58% of the total population. The ideal number of entrepreneurs in the country is 4% of the total population. One solution to reduce unemployment is to increase the number of ntrepreneurs. This study aimed to examine the relationship between the big five personality with the intention of ntrepreneurship, especially in psychology student UMS. This study population is students of Psychology UMS. The sampling technique used in this research is purposive sampling, that the sampling technique based on a certain considerations such as population characteristics or traits that have been previously known. The number of samples taken for this study is as much as 100. The method of data collection that big five personality scale and intention scale entrepreneurship. Based on the analysis results obtained coefficient (r) of 0.596 with p = 0.000 (p<0.01). This means that the hypothesis is proven that the author is significant positive relationship between the big five personality with the intention of entrepreneurship. The effective contribution of big five personality with the intention of entrepreneurship is 41.2%, 58.8% means that there are other variabels that affect the intention of entrepreneurship outside the big five personality variabels. Entrepreneurial intentions had empirical mean is 145.3 and hypothetical average is 114 which means that research on the subject is high. The conclusion of this research is there is a significant positive relationship between the big five personality with the intention of entrepreneurship